The Impact of Summer Vacation on Pupils’Academic Achievement - Sahraoui, Sid Ahmed (My University, 2020)
When it comes to the question of how to enhance student academic achievement in Algeria, the impact of summer vacation is almost entirely missing from the discourse. Little attention is given to the ramifications that long absences from school have on pupils, and to what extent it could hinder or regress their learning outcome. The nine-month calendar is a byproduct of an agrarian era lacking the technological means to deal with the challenges it faced at the time. This research analyzes the impact of summer vacation on pupils. The experience took place two weeks after the coming back of pupils to school after vacations, and before the official starting of the new curriculum. Participants are second-year pupils, each student from two different classes was given a test that is similar to the one they had taken the previous year in the final exam of the third semester. Additionally, a separate interview was arranged with the teachers of both classes on a later date. While the two exams were nearly identical, the average results reveal an alarming gap between the one taken prior, and the one taken after the summer holidays.
The case of Second –Year Pupils at Ben Abd El Malek Ramdane Secondary school of Mostaganem
Keywords: Pupils’ academic achievement; Summer vacation; Learning outcome; Nine-month calendar; Secondary school